Additional Marketing Responses to a Tax on Sugar-Sweetened Beverages; Comment on "Understanding Marketing Responses to a Tax on Sugary Drinks: A Qualitative Interview Study in the United Kingdom, 2019" - Jasmina Ilicic; Stacey Brennan; Katherine Cullerton (Kerman University of Medical Sciences, 2023)
Marketing responses to sugar-sweetened beverage (SSB) taxes are understudied in the literature. Previous research has been limited to examining price and advertising, in particular promotions responses. Forde et al advocate for a focus on exploring a range of marketing responses to a SSB tax, with an emphasis on the marketing mix (price, promotion, product, and place). Their qualitative findings from the United Kingdom focus mostly on possible product and price decisions, with limited discussion of place and promotions decisions. We argue that the proposed marketing mix decisions may be used to avoid or side-step a SSB tax and that their likelihood of adoption may be dependent upon additional factors besides brand strength, reputation, and portfolio size highlighted by Forde and colleagues, such as organizational capabilities, industry competition, and brand positioning. We recommend future research examine the importance of consumer behaviour in developing marketing programs and in response to the marketing mix levers pulled by industry.